Swedish samples : A conversation on contemporary art : Daniel Birnbaum - Christian Chambert - Peter Cornell - Ingela Lind - Gertrud Sandqvist. - Birnbaum, Daniel; Chambert, Christian; Cornell, Peter; Lind, Ingela; Sandqvist, Gertrud (Lund : Propexus, 1994)
This book is based on a conversation between five art critics which took place at the Konstfackskolan (University College of Arts, Crafts and Design) in Stockholm one afternoon in the winter of 1994.
XXVIII IAAC/AICA Congress 1994
boek